The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.labeco.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Does school type affect cognitive and non-cognitive development in children? Evidence from Australian primary schools

Abstract: This paper investigates the effects of primary school choices on cognitive and non-cognitive development in children using data from the Longitudinal Study of Australian Children (LSAC). We militate against the problems associated with individual unobserved heterogeneity by exploiting both the richness of LSAC data and contemporary econometric methods. We find that sending children to Catholic or independent primary schools has no significant effect on their cognitive and non-cognitive outcomes. We now have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 23 publications
7
48
0
Order By: Relevance
“…Raw gender test score gaps at means (estimated from model 1, see the first row of each subject panel in Table 2) show the well-known gender gaps in both maths and reading skills as observed in the literature: male students outperform female students in maths but lag behind with respect to reading (Husain and Millimet 2009;Fryer and Levitt 2010;Nghiem et al 2015;Justman and Méndez 2016). Furthermore, while the gender test score gap in reading is already observed in all grades, the (reverse) gender gap in numeracy only presents in grades 5 and 7.…”
Section: Estimates Of Gender Test Score Gap At Means Of Test Score DImentioning
confidence: 63%
See 2 more Smart Citations
“…Raw gender test score gaps at means (estimated from model 1, see the first row of each subject panel in Table 2) show the well-known gender gaps in both maths and reading skills as observed in the literature: male students outperform female students in maths but lag behind with respect to reading (Husain and Millimet 2009;Fryer and Levitt 2010;Nghiem et al 2015;Justman and Méndez 2016). Furthermore, while the gender test score gap in reading is already observed in all grades, the (reverse) gender gap in numeracy only presents in grades 5 and 7.…”
Section: Estimates Of Gender Test Score Gap At Means Of Test Score DImentioning
confidence: 63%
“…This finding is consistent with our previously observed pattern of girls having higher pre-school cognitive skills. Estimates of the above gender test score gaps also highlight the importance of controlling for students' pre-school cognitive skills, which is the summary of genetic and early childhood investment in the formation of human capital, in the student development as shown in the literature (Todd and Wolpin 2007;Bernal 2008;Cunha et al 2010;Lai 2010;Elder and Jepsen 2014;Fortin et al 2015;Nghiem et al 2015). As previous studies in this literature were unable to control for pre-school cognitive skills-due to the unavailability of such measures in the researchers' data sets-this is a novel empirical result.…”
Section: Or Third Grade Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…Year 5, Nghiem, Nguyen, Khanam, and Connelly (2015) found that the higher scaled scores of students from independent and Catholic schools in Year 5 NAPLAN performance disappear with a comprehensive set of controls that includes prior achievement (Year 3 NAPLAN performance). Unexpectedly, the effects for attending a Catholic school (relative to a government school) were negative and statistically significant for spelling and grammar (Nghiem et al, 2015, p. 60).…”
Section: Introductionmentioning
confidence: 96%
“…Evidence from different datasets, countries, measures of achievement and levels of school (e.g., primary, secondary) have shown that in most instances, any private school academic advantage disappears once the socioeconomic background of students is controlled for. In other words, private schools often have superior outcomes than public schools, but these outcomes are explained by the characteristics of the students that they enrol, not the schools themselves (Lubienski & Lubienski, 2014;Nghiem, Nguyen, Khanam, & Connelly, 2015;OECD, 2011).…”
Section: Introductionmentioning
confidence: 99%